Determinan Profitabilitas Bank Perkreditan Rakyat di Kota Palembang Periode 2013-2018 - Riri Hanifa; Anton Trianto; Mahdi Hendrich (MBIA, 2019)
This study was conducted with the aim to empirically examine the effect of CAR, NPL, BOPO and LDR on profitability (ROA) at the Rural Credit Bank in Palembang for the period 2013-2018. The type of this research is descriptive quantitative The population in the research object is all BPRs contained in Palembang city amounted to 13 BPR while the total sample of 10 BPR. The research sample was taken with a purposive sampling system with the criteria of a BPR whose financial statements were published by the Financial Services Authority in the 2013-2018 period. The method used in this study uses multiple regression analysis with a hypothesis testing tool that is the t test and the F test. However, before conducting multiple regression analysis, the classical assumption test is performed first. Through the simultaneous hypothesis test results (Test F) it is known that CAR, BOPO, NPL and LDR have a significant effect on the profitability of BPR (sig 0,000). While based on the partial hypothesis test results (t test) on BPR shows that CAR variable does not influence ROA (sig 0.183), BOPO variable has no effect on ROA (sig 0.114), NPL variable has significant effect on ROA (sig 0.001) and LDR variable also no effect on ROA (sig 0,782). Adjusted R ² value in the regression model was obtained at 56.1, this indicates that the influence of independent variables on the dependent variable (ROA) was 56.1% while the remaining 43.9% was influenced by other factors outside this study.